The potential use of by products from cold pressed oil industry as natural fat replacers and functional ingredients in salad dressings - Çakmak, Zeynep Hazal Tekin (My University, 2021)
In this study, the potential use of cold-pressed black cumin seed (BOB), coconut (COB), flaxseed (FOB), and pumpkin seed oil by-products (POB) as functional ingredients and natural oil substitutes in low-fat salad dressing was examined. In the first stage of the study, by-product characterization was carried out. For this purpose, physicochemical properties, bioactive properties, and antimicrobial activities, and in-vitro bioaccessibility of TPC (total phenolic compound) of by-products were investigated. FOB and BOB showed higher TPC and CUPRAC (CUPric reducing antioxidant capacity) values and a higher antimicrobial effect than the other samples. In the second stage, the rheological properties of low-fat salad dressings prepared with 1-5% by-products were compared with low-fat and high-fat salad dressing samples in terms of rheological properties. Salad dressings enriched with by-products exhibited shear-thinning (pseudoplastic), viscoelastic solid behavior, and thixotropic properties similar to that of full-fat salad dressings. In the third stage, 17 different formulations were prepared with 1.0-5.0% POB and 0.5-1.5% FOB. Optimum FOB and POB amounts were determined as 1.49% and 3.04%, respectively by response surface methodology (RSM) and full factorial xiv trial design (CCD). In the final stage, high-fat salad dressing (HF-SD), low-fat salad dressing (LF-SD), low-fat salad dressing enriched with BOB (BOBLF-SD), with COB (COBLF-SD), with FOB (FOBLF-SD), and with POB (POBLF-SD) were prepared. The emulsion stability (by thermal loop test and phase separation tests), zeta potential and particle size, microstructure, and oxidative stability of the samples were investigated. Low-fat salad dressings prepared with by-products showed higher IP and G++ and lower S++ values than full-fat and low-fat control samples, indicating that these by-products could improve the oxidative stability of low-fat salad dressings. This study shows that cold-pressed black cumin seed, coconut, flaxseed, and pumpkin seed oil by-products can be used as natural fat substitutes, stabilizers, emulsifiers, and functional ingredients in low-fat salad dressings.

Bu çalışmada, soğuk presleme ile elde edilen çörekotu tohumu (BOB), hindistancevizi (COB), keten tohumu (FOB) ve kabak çekirdeği yağı yan ürünlerinin (POB) az yağlı salata sosunda fonksiyonel bileşen ve doğal yağ ikameleri olarak kullanım potansiyeli araştırılmıştır. Çalışmanın ilk aşamasında yan ürün karakterizasyonu gerçekleştirilmiştir. Bu amaçla, yan ürünlerin fizikokimyasal özellikleri, biyoaktif özellikleri ve antimikrobiyal aktiviteleri ve TFM (toplam fenolik madde) in vitro biyoerişilebilirliği araştırılmıştır. FOB ve BOB, diğer numunelere göre daha yüksek TFM ve CUPRAC (Bakır(II) iyonu indirgeyici antioksidan kapasite) değerleri ve daha yüksek antimikrobiyal etki göstermiştir. İkinci aşamada, %1-5 oranında yan ürünlerle hazırlanan az yağlı salata sosu örneklerinin reolojik özellikleri (akış davranışı, dinamikler ve 3-ITT), düşük yağlı ve yüksek yağlı salata sosu örnekleri ile kıyaslanmıştır. Yan ürünlerle zenginleştirilmiş salata sosu örnekleri, tam yağlı salata sosuna benzer yüksek kesme incelmesi (psödoplastik), viskoelastik katı davranış ve tiksotropik özellikler sergilemiştir. Üçüncü aşamada %1.0-5.0 POB ve %0.5-1.5 FOB ile 17 farklı formülasyon hazırlanmıştır. Yanıt yüzeyi metodolojisi (RSM) ve tam faktöriyel deneme tasarımı (CCD) ile optimum FOB ve POB miktarları sırasıyla %1,49 ve %3,04 olarak belirlenmiştir. Son aşamada, yüksek yağlı salata sosu (HF-SD), az yağlı salata sosu (LF-SD), BOB ile (BOBLF-SD), COB ile (COBLF-SD), ile FOB (FOBLF-SD) ve POB ile zenginleştirilmiş az yağlı salata sosu (POBLF-SD) hazırlanmıştır. Örneklerin emülsiyon stabilitesi (termal döngü testi ve faz ayırma testleri ile), zeta potansiyeli ve partikül boyutu, mikroyapı ve oksidatif stabilitesi incelenmiştir. Yan ürünlerle hazırlanan az yağlı salata sosu numuneleri, tam yağlı ve az yağlı kontrol numunelerine göre daha yüksek IP ve G++ ve daha düşük S++ değerleri göstermiştir, bu da yan ürünlerin az yağlı salata soslarının oksidatif stabilitesini iyileştirebileceğini göstermiştir. Bu çalışma, soğuk presleme ile elde edilen çörekotu tohumu, hindistancevizi, keten tohumu ve kabak çekirdeği yağı yan ürünlerinin az yağlı salata soslarında doğal yağ ikameleri, stabilizatörler, emülgatörler ve fonksiyonel bileşenler olarak kullanılabileceğini göstermektedir.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2021
Keywords: Cold pressed; By-products; Low-fat salad dressing; Rheology; In-vitro bioaccessibility; Soğuk presleme; Düşük yağlı salata sosu; Reoloji; In-vitro biyo-erişilebilirliği